2015
DOI: 10.4103/0975-9476.146563
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of the role of tulsi and turmeric in the management of oral submucous fibrosis: A pilot, prospective observational study

Abstract: The aim of the present study was to investigate the clinical efficacy of herbal medicines (1 gm tulsi and 1 gm turmeric mixed in glycerine base) for the treatment of oral submucous fibrosis (OSMF). Forty-one patients in the age group of 17- 56 years without any systemic complications were included in the study. The patients were treated with medicines, which were to be applied 3-4 times a day. Blood samples were collected before and after treatment to screen for any systemic changes due to these medications. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(7 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…Various studies are stated in the literature with significant mean improvement in mouth opening using levamisole (2.9 mm), antoxid (3.1 mm), lycopene (3.4 mm, 5.38 mm), lycopene with Vitamin E (6.2 mm), pentoxifylline (7 mm), pentoxifylline with garlic pearls (5 mm), turmeric with tulsi (3–4 mm), and turmeric with black pepper (3.8 mm). [81416171819] Group A patients in the present study have shown equivalent results to antoxid, levamisole, turmeric with tulsi, and turmeric with black pepper. Group B patients have shown comparable results to lycopene, lycopene with Vitamin E, and pentoxifylline with garlic pearls.…”
Section: Discussionsupporting
confidence: 54%
“…Various studies are stated in the literature with significant mean improvement in mouth opening using levamisole (2.9 mm), antoxid (3.1 mm), lycopene (3.4 mm, 5.38 mm), lycopene with Vitamin E (6.2 mm), pentoxifylline (7 mm), pentoxifylline with garlic pearls (5 mm), turmeric with tulsi (3–4 mm), and turmeric with black pepper (3.8 mm). [81416171819] Group A patients in the present study have shown equivalent results to antoxid, levamisole, turmeric with tulsi, and turmeric with black pepper. Group B patients have shown comparable results to lycopene, lycopene with Vitamin E, and pentoxifylline with garlic pearls.…”
Section: Discussionsupporting
confidence: 54%
“…Various modern forms (capsules, tablets, lozenges) of dietary supplements containing turmeric, and its bioactive compounds are commercially available. Turmeric powder with glycerin has been used in the treatment of a burning sensation in oral submucous fibrosis [182]. An ointment containing 10% alcohol extract from turmeric roots is effective in the treatment of ulcers caused by aspirin [183].…”
Section: Conclusion and Future Outlookmentioning
confidence: 99%
“…Clinical features include blanching of the oral mucosa, limited mouth opening, restriction of tongue movements, burning sensation, etc. [18,19]. Through its antioxidant property and immunomodulatory effect, it produced a significant release in the burning sensation when studied clinically [18].…”
Section: Oral Submucous Fibrosis :-mentioning
confidence: 99%